Mechanisms of ubiquitylation of the mitotic regulatory protein Cdc20 - Danielle Sitry-Shevah; Shirly Miniowitz-Shemtov; Tania Liburkin Dan; David Barford; Avram Hershko (Proceedings of the National Academy of Sciences, 2026)
A multisubunit ubiquitin ligase called the anaphase-promoting complex/cyclosome (APC/C) controls progress through mitosis in eukaryotic cells. The activity of APC/C in mitosis is subject to both positive and negative regulation by the co-activator protein Cdc20. On exit from mitosis, Cdc20 is targeted for degradation by APC/C-catalyzed ubiquitylation. It has been proposed that the ubiquitylation of Cdc20 is carried out by an intramolecular “cis” mechanism, in which Cdc20 bound to the co-activator site of APC/C is directly ubiquitylated [I. T. Foe et al. , Curr. Biol. 21 , 1870–1877 (2011)]. This proposal was mainly based on the observation that mutation in the IR tail of Cdc20, an isoleucine-arginine C-terminal sequence involved in its binding to APC/C, markedly impaired Cdc20 ubiquitylation. We find that the IR tail of Cdc20 is also required for Cdc20 ubiquitylation promoted by Cdh1, an APC/C co-activator that acts in the G1 phase of the cell cycle. This suggested the involvement of the IR motif in a trans mechanism of Cdc20 ubiquitylation. A trans mechanism is also suggested by the observation that Cdc20 ubiquitylation by APC/C Cdc20 , as that by APC/C Cdh1 , requires both KEN-box and CRY-box degrons of Cdc20. A model is proposed according to which the IR tail of substrate Cdc20, along with its KEN-box and CRY-box motifs, interact with corresponding binding sites of APC/C-coactivator complexes.